A digital library for education: the PEN-DOR project. - Fullerton K; Greenberg J; McClure M; Rasmussen E; Stewart D (Electronic Library, 1999)
Recent initiatives in digital library research have suggested new models for the creation and organisation of digital information and its dissemination to virtual communities. PEN-DOR (the Pennsylvania Education Network Digital Object Repository) is a digital library designed to provide access to the collective experience of teachers, students and administrators in public schools in building lesson plans and using curriculum materials. Using the WWW as a platform, PEN-DOR incorporates current research in digital libraries to provide K-12 educators with access to multimedia resources and tools to create new lesson plans and presentations, and to modify existing ones. Design problems addressed by the project include the design of a distributed, object-oriented database architecture, the description and cataloguing of multimedia objects, and issues related to usability and training for a geographically scattered user community. Two critical aspects of the organisation of this digital library are the development of a method for the persistent identification of resources, and the design of a record structure based on recent developments in metadata. Resource identification has been achieved by adopting a system-wide approach with an upgrade path to the emerging URN standards. In designing a record structure, the PEN-DOR project has elected to use the GEM (Gateway to Educational Materials) metadata standard developed as part of the GEM union catalogue project. Content for the database is solicited from project partners, government agencies and educational resources Web sites, as well as from participating teachers. Once incorporated in the repository, materials can be organised in frameworks that form the basis for lessons, tutorials and presentations. As frameworks arse developed, used, critiqued and modified, they will form a community memory of past experience. Supported by the state's Link-to-Learn programme, the system will function as a resource for educators throughout Pennsylvania.